Fe-Sn-Cu ternary mixed oxide catalyst, preparation method thereof and application of Fe-Sn-Cu ternary mixed oxide catalyst in catalysis of B-V reaction
By developing the Fe-Sn-Cu ternary mixed oxide catalyst, the problem of poor catalytic effect of existing catalysts in Baeyer-Villiger oxidation reaction is solved, and efficient conversion of ketones and aldehydes is achieved, with high yield and stable yield.
Patent Information
- Application Number
- CN202411915576.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing catalysts have poor catalytic effects in Baeyer-Villiger oxidation reaction, and are complex or simple in preparation but lack the effect, making it difficult to meet the needs of industrial applications.
A Fe-Sn-Cu ternary mixed oxide catalyst was developed, and a mixed salt solution of Fe(NO3)3·9H2O, SnCl4·5H2O and Cu(NO3)2·3H2O was dropped into Na2CO3 to precipitate. After high temperature calcination, the Fe-Sn-Cu catalyst was obtained, which was used to catalyze the Baeyer-Villiger oxidation reaction.
The catalyst has a high conversion rate for ketones and aldehydes under mild conditions, high yields for esters and acids, and is simple to prepare and easy to recover. The effect of 5 cycles remains unchanged.
Smart Images

Figure CN119701981A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials and relates to a Fe-Sn-Cu ternary mixed oxide catalyst and a preparation method thereof and application in catalyzing Baeyer-Villiger (BV) oxidation reaction. Background Art
[0002] Baeyer-Villiger oxidation reaction (BV oxidation reaction for short) is an important type of organic synthesis reaction that converts ketones into corresponding esters or lactones. This reaction was first discovered by chemists in 1899. After more than a hundred years of exploration, scientists have developed many methods to synthesize simple ketones or cyclic ketones into high-value esters or lactones. Moreover, these esters or lactones have high regional and spatial selectivity and can be used as key intermediates for the preparation of drugs, pesticides, dyes and other fine chemical products. Due to its own characteristics, BV oxidation reaction has become an important cornerstone reaction in the field of chemical synthesis and has attracted a lot of research for a long time. Traditional oxidants include peroxyacids and peroxyorganic alcohols, among which peroxyacids are highly corrosive to equipment and peroxyorganic alcohols are expensive. Hydrogen peroxide and molecular oxygen are relatively environmentally friendly oxidants and have gradually attracted the attention of scientific researchers. However, hydrogen peroxide is easy to decompose, the generated water is easy to decompose lactones, and it is inconvenient to transport. O2 is a relatively clean oxidant. Using O2 as an oxidant to oxidize cyclohexanone to synthesize ε-caprolactone is economical, safe, and has fewer by-products, which is in line with the current development trend of green chemistry. Most of the catalysts reported for BV oxidation today have good catalytic effects but are complicated to prepare, or are simple to prepare but lack catalytic effects. For example, the copper oxide-modified SBA-15 catalyst synthesized by MPAthira et al. using the impregnation method can achieve a cyclohexanone conversion rate of 63% and an ε-caprolactone selectivity of 96% at 50°C for 5 hours.
[0003] Metal oxide catalysts are usually complex oxides, that is, multi-component oxides. At least one of the components is a transition metal oxide. The components may interact with each other, and the interaction varies depending on the conditions. Complex oxide systems usually have multiple phases coexisting, such as MoO3-Al2O3, which has α - , β - , γ -Phase. Its structure is very complex, including solid solution, heteropoly acid, mixed crystal, etc. In terms of catalytic action and function, some components are main catalysts, and some components are co-catalysts or carriers. Transition metal oxide catalysts developed relatively late. In 1913, vanadium pentoxide was used in sulfuric acid industry as a catalyst for the oxidation of sulfur dioxide to sulfur trioxide; in 1916, vanadium catalyst was used for naphthalene oxidation to produce phthalic anhydride; in the early 1920s, zinc-chromium oxide was used to produce methanol from synthesis gas; in the 1960s, with the development of petrochemical industry, especially in 1960, the use of molybdenum-bismuth oxide as a catalyst to successfully oxidize propylene to acrylonitrile, both in terms of catalyst varieties and basic theoretical research, oxide catalysts have been greatly developed. However, most of the metal oxide catalysts reported so far are binary, and there are few reports on ternary mixed oxide catalysts. The ternary catalyst has better catalytic effect, is more stable, and is simple to prepare, and has a good development prospect.
[0004] Based on the above problems, it is urgent to develop a ternary catalyst suitable for the BV oxidation reaction of ketones, which is simple to prepare, has good catalytic effect and is stable. Summary of the invention
[0005] The purpose of the present invention is to provide an application of a Fe-Sn-Cu ternary mixed oxide in a Baeyer-Villiger (BV) oxidation reaction.
[0006] The technical solution of the present invention is to provide an application of a Fe-Sn-Cu ternary mixed oxide in a Baeyer-Villiger (BV) oxidation reaction and an application method thereof, wherein ketone is used as a substrate, aldehyde is used as a co-oxidant, oxygen is used as a green oxidant, and Fe-Sn-Cu is used as a catalyst. The reaction conditions are mild, the conversion rates of ketones and aldehydes are high, the yields of esters and acids are high, the catalyst is simple to prepare and easy to recycle and utilize, the catalytic effect temperature is low, and the effect remains unchanged after five cycles. The catalyst is a Fe-Sn-Cu ternary mixed oxide.
[0007] The specific technical solution for implementing the present invention is:
[0008] A method for catalyzing a BV reaction using an Fe-Sn-Cu catalyst comprises the following steps: sequentially mixing the Fe-Sn-Cu catalyst, a solvent, ketones and a co-oxidant aldehyde, introducing oxygen, stirring and heating, separating the Fe-Sn-Cu catalyst after the reaction is completed, and subjecting the reaction liquid to reduced pressure distillation to obtain a product.
[0009] In some preferred embodiments, the Fe-Sn-Cu catalyst is used to drop a mixed salt solution of Fe(NO3)3·9H2O, SnCl4·5H2O, and Cu(NO3)2·3H2O into Na2CO3 to precipitate a mixed precipitate of Fe(OH)3, Cu(OH)2, and Sn(OH)4. After high-temperature calcination, OH - Leave, and form Fe2O3, SnO2, CuO mixed oxide, i.e., Fe-Sn-Cu catalyst;
[0010] and / or
[0011] The Fe-Sn-Cu catalyst is a ternary mixed oxide; and / or
[0012] The Fe-Sn-Cu catalyst 3+ Sn 4+ , Cu 2+ The molar ratio is 1:1:(0.01-0.5), preferably 1:1:0.1; and / or
[0013] The pores of the Fe-Sn-Cu catalyst are disordered; and / or
[0014] The pores of the Fe-Sn-Cu catalyst are mesopores with a size of 2 to 40 nm; and / or
[0015] The specific surface area of the Fe-Sn-Cu catalyst is 7 to 9 m 2 ·g -1
[0016] The Fe-Sn-Cu catalyst has a sheet structure.
[0017] In some preferred embodiments, the ketone is selected from any one or a combination of two or more of the following groups: cyclohexanone, 2-methylcyclohexanone, cyclopentanone, adamantane ketone; and / or
[0018] The aldehydes are selected from any one or a combination of two or more of the following groups: benzaldehyde, 4-methylbenzaldehyde, tert-butylaldehyde; and / or
[0019] The solvent is selected from 1,2-dichloroethane and / or sec-butyl acetate.
[0020] In some preferred test schemes, the mass of the Fe-Sn-Cu catalyst is 4% to 10% of the mass of the ketone.
[0021] In some preferred embodiments, the conditions of the BV reaction include:
[0022] The reaction temperature is 45 to 65°C; and / or
[0023] The reaction time is 4 to 7 hours; and / or
[0024] The oxygen flow rate is 15-30 mL / min.
[0025] In some preferred embodiments, the ratio of the amount of cyclohexanone to the solvent is 1 g: (4-15) mL; that is, the amount of the cyclohexanone to the solvent is 1 / g: (5-20) / g; and / or
[0026] The molar ratio of the ketones to the aldehydes is 1:(1.5-3).
[0027] In a second aspect, the present invention provides a Fe—Sn—Cu catalyst.
[0028] In a third aspect, the present invention provides a use of the Fe-Sn-Cu catalyst in catalyzing a BV reaction.
[0029] In a fourth aspect, the present invention further provides a method for preparing the Fe-Sn-Cu catalyst, comprising the following steps:
[0030] 1) Prepare a mixed salt solution of Fe(NO3)3·9H2O, SnCl4·5H2O, and Cu(NO3)2·3H2O;
[0031] 2) adding the mixed salt solution dropwise to the Na2CO3 solution at 40-70°C, preferably at 60°C, and continuously stirring, adding NaOH solution to adjust the pH after the mixed salt solution is completely added, continuing stirring, aging, filtering, drying, and grinding to obtain powder A;
[0032] 3) Powder A is calcined at high temperature in a muffle furnace and sieved to obtain a Fe-Sn-Cu catalyst.
[0033] The molar ratio of the ferric nitrate nonahydrate, the tin tetrachloride pentahydrate and the copper nitrate trihydrate is 1:1:(0.01-0.5); and / or
[0034] The volume of the mixed salt solution is 100-300 mL; and / or
[0035] The volume ratio of the NaCO3 solution to the mixed salt solution is 1:(0.5-2); and / or
[0036] In the step 2), the mass fraction of the NaCO3 solution is 3% to 7%, preferably 5%; and / or
[0037] In the step 2), the stirring time is continued for 1 to 3 hours, the aging time is 24 to 48 hours, and the aging temperature is 50 to 70° C.; and / or
[0038] In the step 2), the concentration of the NaOH solution is 1-2 mol / L, and the pH is 10; and / or
[0039] In the step 3), the high temperature calcination temperature is 700-900° C., and the screening particle size ranges are 40-60 mesh, 80-100 mesh, and 120-160 mesh.
[0040] The beneficial effects of the present invention are:
[0041] (1) The Fe-Sn-Cu ternary mixed oxide catalyst of the present invention is easy to prepare and has a good catalytic effect not only on ketones, but also on aldehydes in parallel reactions. The ketone conversion rate can reach up to 99%, the ester yield can reach up to 99%, the aldehyde conversion rate can reach up to 98%, and the acid yield can reach up to 92%. At the same time, it has good stability and maintains good catalytic activity after 5 cycles.
[0042] (2) The Fe-Sn-Cu catalyst of the present invention has mild reaction conditions for catalytic oxidation of ketones to generate esters, does not require high temperature and high pressure, uses less solvent, uses less co-oxidant, and requires less catalyst, thus greatly saving costs.
[0043] (3) The present invention uses oxygen as an oxidant, which is green and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Scanning electron microscope photo and electron spectrum of Fe-Sn-Cu-1 catalyst sample particles;
[0045] Figure 2 XPS spectrum of Fe-Sn-Cu-1 catalyst;
[0046] Figure 3 XRD spectra of Fe-Sn-Cu at different ratios;
[0047] Figure 4 Infrared spectra of Fe-Sn-Cu at different ratios;
[0048] Figure 5 N2- adsorption-desorption diagram (A) and pore size distribution diagram (B) of Fe-Sn-Cu at different ratios. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with specific implementation modes.
[0050] Preparation of catalyst materials
[0051] Example 1
[0052] 1) Add 12.12 g Fe(NO3)3·9H2O, 10.51 g SnCl4·5H2O and 0.72 g CuO·3H2O to 150 ml deionized water, stir and dissolve to obtain a mixed salt solution;
[0053] 2) Prepare 150 ml of 5% Na2CO3 solution, stir and heat to 60°C in a three-necked flask, drop the mixed salt solution into the Na2CO3 solution, and continue stirring. After all the solution is added, add 2 mol / L NaOH solution until the pH is 10, continue stirring at 60°C for 2 hours, and age in an oven at 60°C for 48 hours after the stirring is completed. After the aging is completed, filter, wash, dry and grind to obtain powder A;
[0054] 3) Powder A was calcined at 850° C. for 5 h in a muffle furnace, and particles of 80 to 100 mesh were sieved to obtain a Fe-Sn-Cu-1 catalyst.
[0055] Attached Figure 1 This is a scanning electron microscope photo and electron map of the Fe-Sn-Cu-1 catalyst sample particles. From the SEM image, it can be seen that it is a flaky material with prismatic particles on the surface. The accumulation of prismatic particles is looser than the aggregation of smooth particles, which has a certain promoting effect on the activity of the catalyst. From the EDX element map, it can be seen that the tin element accounts for the highest proportion, and the X-ray intensity of the iron, tin and copper signals is uniform, indicating that their distribution is uniform.
[0056] Attached Figure 2 The XPS spectrum of the Fe-Sn-Cu-1 catalyst. The elemental composition and valence state of the elements can be clearly understood through the determination of the binding energy of the XPS analysis. Figure A shows the measured spectrum of the Fe-Sn-0.1Cu system, depicting the presence of iron, tin and copper. According to the C1S binding energy peak located at 284.8eV, the binding energy values of Fe, Sn, O and Cu were calibrated. The most common peaks of 710.0eV and 723.7eV and the satellite peak of 716.12eV (Figure B) can be attributed to the Fe(II) configuration. The peaks with binding energies of 933.5eV and 953.2eV correspond to Cu 2p3 / 2 and Cu 2p1 / 2, respectively (Figure C), which confirms the +2 valence state of copper and its presence as isolated CuO. In addition, the XPS spectrum of tin with peaks at 487.4eV and 496.6eV in Figure D proves the presence of the tin(IV) configuration.
[0057] Example 2
[0058] Based on Example 1, the step 1) is modified into the following steps:
[0059] 1) Add 12.12 g Fe(NO3)3·9H2O, 10.51 g SnCl4·5H2O and 0.36 g CuO·3H2O to 150 ml deionized water, stir and dissolve to obtain a mixed salt solution;
[0060] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Cu-2 catalyst.
[0061] Example 3
[0062] Based on Example 1, the step 1) is modified into the following steps:
[0063] 1) Add 12.12 g Fe(NO3)3·9H2O, 10.51 g SnCl4·5H2O and 3.6 g CuO·3H2O to 150 ml deionized water, stir and dissolve to obtain a mixed salt solution;
[0064] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Cu-3 catalyst.
[0065] Comparative Examples 1 to 3, as shown in the attached Figure 3 The following are XRD spectra of Fe-Sn-Cu at different ratios. The phase analysis was performed using Jade-6. The three characteristic peaks of the Fe-Sn-Cu catalyst (2θ is 26.693°, 33.960°, 51.860°) are completely consistent with the three characteristic peaks of SnO2 (PDF#41-1445), which correspond to the crystal planes (110), (101) and (211) respectively. With the increase of CuO, the three characteristic peaks of Fe2O3 (2θ=24.531°, 33.160°, 54.120°) gradually decrease, and the characteristic peaks of CuO (2θ=35.602°, 38.816°) gradually increase, and CuO gradually replaces the Fe2O3 lattice position. Through XRD spectrum analysis, the Fe-Sn-Cu catalyst is supported by SnO2, and Fe2O3 and CuO are supported on the SnO2 support.
[0066] Attached Figure 4 This is the infrared spectrum of Fe-Sn-Cu at different ratios. The vibration absorption peak of Fe-O is at 500cm -1 The fingerprint area near 1400-1700cm -1 The vibration absorption peak between 527cm and 527cm is unique to Sn-O. -1 The absorption peak at is the stretching vibration of Cu-O.
[0067] Attached Figure 5The N2 adsorption-desorption diagram (A) and pore size distribution diagram (B) of Fe-Sn-Cu with different ratios. The surface area and porosity of the synthesized material were determined by N2 adsorption-desorption analysis (BET). The adsorption-desorption isotherm (Figure A) shows a typical IV type isotherm and H3 type hysteresis loop, and there is no obvious saturated adsorption platform, indicating that the pore structure is irregular. Combined with the SEM image, it can be seen that it is a flat slit structure. The appearance of the H3 type hysteresis loop is due to the fact that the flaky particle material does not show adsorption saturation in the high relative pressure area. As shown in Figure B, the pore size of the three catalysts is about 30nm. They are mesoporous materials. The larger pore size will expose more active sites of the catalyst, thereby improving the catalytic activity, and it is not easy to clog the catalyst after the reaction, so the number of catalyst cycles will be greatly increased.
[0068] Example 4
[0069] Based on Example 1, the step 1) is modified into the following steps:
[0070] 1) Add 12.12 g Fe(NO3)3·9H2O and 10.51 g SnCl4·5H2O to 150 ml deionized water, stir and dissolve to obtain a mixed salt solution;
[0071] The other steps are the same as those in Example 1 to obtain a Fe-Sn catalyst. By replacing different metal salts, Cu-Sn, Fe-Cu, Ce-Sn, and Co-Sn catalysts can be obtained.
[0072] Example 5
[0073] Based on Example 1, the step 1) is modified into the following steps:
[0074] 1) Add 12.12 g Fe(NO3)3·9H2O, 10.51 g SnCl4·5H2O and 0.87 g Co(NO3)2·6H2O to 150 ml deionized water, stir and dissolve to obtain a mixed salt solution;
[0075] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Co catalyst.
[0076] Example 6
[0077] Based on Example 1, the step 1) is modified into the following steps:
[0078] 1) Add 12.12 g Fe(NO3)3·9H2O, 10.51 g SnCl4·5H2O and 0.76 g Mg(NO3)2·6H2O to 150 ml deionized water and stir to dissolve to obtain a mixed salt solution;
[0079] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Mg catalyst. Cr-Co-Sn and Fe-Ce-Sn catalysts can be obtained by replacing different metal salts.
[0080] Example 7
[0081] Based on Example 1, the step 3) is modified into the following steps:
[0082] 3) Powder A was calcined in a muffle furnace at 800°C for 5 h, and particles of 80-100 mesh were sieved out.
[0083] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Cu-4 catalyst.
[0084] Example 8
[0085] Based on Example 1, the step 3) is modified into the following steps:
[0086] 3) Powder A was calcined at 900°C in a muffle furnace for 5 h, and particles of 80-100 mesh were sieved out.
[0087] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Cu-5 catalyst.
[0088] Example 9
[0089] Based on Example 1, the step 3) is modified into the following steps:
[0090] 3) Powder A was calcined in a muffle furnace at 850°C for 5 h, and particles of 40-60 mesh were sieved out.
[0091] The other steps are the same as those in Example 1 to obtain a Fe-Sn-Cu-6 catalyst.
[0092] Example 10
[0093] With reference to the catalyst for preparing ε-caprolactone by co-oxidation of toluene, its preparation method and application (application number: 202310496094.5), the catalyst VCo-in-CNT-out-FeSn was prepared.
[0094] Embodiment 11
[0095] With reference to a Fe@Sn-NMC catalyst, a preparation method thereof and use in catalyzing BV reaction (application number: 202411337685.9), the catalyst Fe@Sn-NMC was prepared.
[0096] Determination of cyclohexanone conversion and ε-caprolactone yield
[0097] Detection method:
[0098] The catalyst material prepared by the above different embodiments, cyclohexanone, benzaldehyde and 1,2-dichloroethane were added to a 50 mL three-necked flask, oxygen was introduced by bubbling method, the introduction rate of oxygen was adjusted, the reaction was carried out under stirring, and the temperature and time of the stirring reaction were controlled. After the reaction was completed, the catalyst was filtered and separated, and the product was weighed and analyzed by gas chromatography. The conversion rate of cyclohexanone and the yield of ε-caprolactone, the conversion rate of benzaldehyde and the yield of benzoic acid were calculated. The catalyst after separation was washed with a solvent and then dried, and the reaction was repeated again for a cycle test.
[0099] The samples were tested by the internal standard method, and cyclohexanone, ε-caprolactone, benzaldehyde and benzoic acid were calibrated.
[0100] Relative correction factor calculation formula:
[0101]
[0102] f i Represents the relative correction factor of the component to be measured, m i Indicates the mass of the component to be tested, A i Represents the peak area of the component to be tested, m s Indicates the mass of the internal standard, A s represents the peak area of the internal standard.
[0103] The cyclohexanone conversion (C1) was calculated as follows:
[0104]
[0105] m1 represents the mass of unconverted cyclohexanone, m2 represents the total mass of cyclohexanone input, f1 represents the relative correction factor of cyclohexanone, A1 represents the peak area of cyclohexanone, A s represents the peak area of the internal standard, m s Indicates the mass of the added internal standard.
[0106] The selectivity of ε-caprolactone (S1) was calculated as follows:
[0107]
[0108] m3 represents the mass of ε-caprolactone generated, m4 represents the mass of ε-caprolactone generated theoretically from the converted cyclohexanone, m2 represents the total mass of cyclohexanone input, C1 represents the conversion rate of cyclohexanone, f2 represents the relative correction factor of ε-caprolactone, A2 represents the peak area of ε-caprolactone, A s represents the peak area of the internal standard, m s Indicates the mass of the added internal standard.
[0109] The yield (Y1) of ε-caprolactone is calculated as follows:
[0110] Y1=C1×S1
[0111] Table 1
[0112]
[0113]
[0114] By comparing and analyzing the above table, it can be seen that the Fe-Sn-Cu-1 ternary mixed oxide catalyst prepared by the method of the present invention in Example 1 is simple to prepare, and has a good catalytic effect not only on ketones, but also on aldehydes in parallel reactions, with a cyclohexanone conversion rate of 99%, an ε-caprolactone yield of 99%, a benzaldehyde conversion rate of 98%, and a benzoic acid yield of 92%. In addition, the catalyst has good stability and maintains good catalytic activity after 5 cycles.
[0115] In the above table, other examples 4 to 6 respectively use other binary or ternary metals to prepare different catalysts, which cannot have the above-mentioned good conversion rate or yield. On the basis of iron-based and tin-based, Cu 2+ The addition of a small amount of Cu 2+ with Fe 3+ Sn 4+ The synergistic effect between them is far greater than that of other metal ions.
[0116] Among them, the cyclohexanone conversion rate of the Ce-Sn catalyst was as low as 22%, and the benzaldehyde conversion rate was only 19%, which was about 4 times lower than that in Example 1; the conversion rate and yield of the catalytic results of other catalysts also showed a significant downward trend.
[0117] Table 2
[0118]
[0119]
[0120] From the above table, we can see that Fe 3+ Sn 4+ , Cu 2+ When the molar ratio of is 1:1:(0.01-0.5), the catalyst prepared thereby has the best catalytic effect on BV reaction.
[0121] Among them, 12.12g Fe(NO3)3·9H2O, 10.51g SnCl4·5H2O and 0.72g CuO·3H2O, i.e., Fe 3+ Sn 4+ , Cu 2+The optimal molar ratio is 1:1:0.1. In Example 3, too much amount is added, resulting in a significant reduction in the catalytic effect.
[0122] During the catalyst preparation process, the high temperature calcination temperature is controlled at 700-900°C, and the sieved particle size range is 40-60 mesh, 80-100 mesh, and 120-160 mesh. The prepared catalyst can achieve good catalytic BV reaction effect. When the temperature is controlled at 850°C and calcined for 5 hours, the particles of 80-100 mesh are sieved out, and the catalyst has the best catalytic effect.
[0123] Table 3
[0124]
[0125] In the above table, the effects of the examples prepared in the present application on catalyzing the BV reaction with the catalysts loaded with metals on the carrier disclosed in the prior art were compared, and it was found that the effects of other metal-loaded catalysts prepared on different carriers were lower than that of the present application.
[0126] Table 4
[0127]
[0128] Table 5
[0129]
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for catalyzing a Baeyer-Villiger reaction using a Fe-Sn-Cu ternary mixed oxide catalyst, comprising: The Fe-Sn-Cu catalyst, solvent, ketones and co-oxidant aldehydes are sequentially mixed, oxygen is introduced, and the mixture is stirred and heated. After the reaction is completed, the Fe-Sn-Cu catalyst is separated, and the reaction solution is subjected to reduced pressure distillation to obtain the product.
2. The method for catalyzing BV reaction using a Fe-Sn-Cu catalyst according to claim 1, wherein: The Fe-Sn-Cu catalyst is a regular tetrahedral structure of SnO2. 3+ , Cu 2+ , O 2- A Fe-Sn-Cu ternary mixed oxide catalyst dispersed on the surface; and / or The Fe-Sn-Cu catalyst is a ternary mixed oxide; and / or The Fe-Sn-Cu catalyst 3+ Sn 4+ , Cu 2+ The molar ratio is 1:1:(0.01-0.5), preferably 1:1:0.1; and / or The pores of the Fe-Sn-Cu catalyst are disordered; and / or The pores of the Fe-Sn-Cu catalyst have a pore size of 2 to 40 nm; and / or The specific surface area of the Fe-Sn-Cu catalyst is 7 to 9 m 2 ·g -1 ; and / or The Fe-Sn-Cu catalyst has a sheet structure.
3. The method for catalyzing the Baeyer-Villiger reaction using a Fe-Sn-Cu catalyst according to claim 1, wherein: The ketone is selected from any one or a combination of two or more of the following groups: cyclohexanone, 2-methylcyclohexanone, cyclopentanone, and adamantane ketone; and / or The aldehydes are selected from any one or a combination of two or more of the following groups: benzaldehyde, 4-methylbenzaldehyde, tert-butylaldehyde; and / or The solvent is selected from 1,2-dichloroethane and / or sec-butyl acetate.
4. The method for catalyzing the Baeyer-Villiger reaction using a Fe-Sn-Cu catalyst according to claim 1, wherein: The mass of the Fe-Sn-Cu catalyst is 4% to 10% of the mass of the ketones.
5. The method for catalyzing the Baeyer-Villiger reaction using a Fe-Sn-Cu catalyst according to claim 1, wherein: The conditions of the Baeyer-Villiger reaction include: The reaction temperature is 45 to 65°C; and / or The reaction time is 4 to 7 hours; and / or The oxygen flow rate is 15-30 mL / min.
6. The method for catalyzing the Baeyer-Villiger reaction using a Fe-Sn-Cu catalyst according to claim 1, wherein: The ratio of cyclohexanone to solvent is 1g: (4-15)ml; and / or The molar ratio of the ketones to the aldehydes is 1:(1.5-3).
7. An Fe-Sn-Cu catalyst as claimed in any one of claims 1 to 6.
8. Use of the Fe-Sn-Cu catalyst according to claim 7 in catalyzing the Baeyer-Villiger reaction.
9. A method for preparing the Fe-Sn-Cu catalyst according to claim 7, comprising the following steps: 1) Prepare a mixed salt solution of Fe(NO3)3·9H2O, SnCl4·5H2O, and Cu(NO3)2·3H2O; 2) adding the mixed salt solution dropwise to the Na2CO3 solution and stirring continuously, adding NaOH solution to adjust the pH after the mixed salt solution is completely added, continuing stirring, aging, filtering, drying, and grinding to obtain powder A; 3) Powder A is calcined at high temperature in a muffle furnace and sieved to obtain a Fe-Sn-Cu catalyst.
10. The method for preparing the Fe-Sn-Cu catalyst according to claim 9, wherein: The molar ratio of the ferric nitrate nonahydrate, the tin tetrachloride pentahydrate and the copper nitrate trihydrate is 1:1:(0.01-0.5); and / or In the step 2), the volume ratio of the NaCO3 solution to the mixed salt solution is 1:(0.5-2); and / or In the step 2), the mass fraction of the NaCO3 solution is 3% to 7%, preferably 5%; and / or In the step 2), the stirring time is continued for 1 to 3 hours, the aging time is 24 to 48 hours, and the aging temperature is 50 to 70° C.; and / or In the step 2), the concentration of the NaOH solution is 1-2 mol / L, and the pH is 10; and / or In the step 3), the high temperature calcination temperature is 700-900° C., and the screening particle size ranges are 40-60 mesh, 80-100 mesh, and 120-160 mesh.
Citation Information
Patent Citations
Catalyst for preparing epsilon-caprolactone through toluene co-oxidation as well as preparation method and application of catalyst
CN116870918A
Fe (at) Sn-NMC catalyst, preparation method thereof and application of Fe (at) Sn-NMC catalyst in catalysis of B-V reaction
CN119215952A